Photodynamic Inactivation of Antigenic Determinants of Single-Stranded DNA Bacteriophage φX174 - Khan, Narayan C. (1974)
Bacteriophage φX174 when photodynamically inactivated (i.e., when rendered unable to produce plaques as a result of exposure to visible light in air in the presence of proflavine) progressively lost their capacity to bind efficiently with homologous antiserum. Such loss of serum-blocking power was evident with heat-inactivated but not with UV-irradiated phage. The ability of the phages to adsorb to host cells, however, remained practically unaltered even after photodynamic inactivation. It thus appears that photodynamic damages in the so-called “jacket” component of the φX174 coat proteins are partly responsible for the loss of plaque-forming ability, whereas the “spikes” are either poor antigens or insensitive to photodynamic treatment.